2015
DOI: 10.1007/s00246-015-1158-9
|View full text |Cite
|
Sign up to set email alerts
|

Critical Congenital Heart Diseases in Preterm Neonates: Is Early Cardiac Surgery Quite Reasonable?

Abstract: Prematurity is a recognized risk factor for morbidity and mortality following cardiac surgery. Postoperative and long-term outcomes after cardiac surgery performed in the preterm period are poorly described. The aim of this study was to analyze a population of preterm neonates operated on for critical congenital heart disease (CHD) before 37 weeks of gestational age (wGA) with special attention given to early and late mortality and morbidity. Between 2000 and 2013, 28 preterm neonates (median gestational age (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Prematurity also manifests as multiple extracardiac detriments, including difficulties in postoperative management associated with low body weight (at birth or at initial palliation), respiratory distress syndrome, bronchopulmonary dysplasia, pulmonary hypertension, genetic abnormality, and hepatorenal dysfunction. [1][2][3][4] These issues may persist even long after the initial palliation and may lead to attrition from the Fontan track. [5][6][7] Research has demonstrated that the deleterious effect of younger GA applies not only to premature infants but also to the neonates born at early term.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Prematurity also manifests as multiple extracardiac detriments, including difficulties in postoperative management associated with low body weight (at birth or at initial palliation), respiratory distress syndrome, bronchopulmonary dysplasia, pulmonary hypertension, genetic abnormality, and hepatorenal dysfunction. [1][2][3][4] These issues may persist even long after the initial palliation and may lead to attrition from the Fontan track. [5][6][7] Research has demonstrated that the deleterious effect of younger GA applies not only to premature infants but also to the neonates born at early term.…”
Section: Commentmentioning
confidence: 99%
“…However premature and early-term birth (ie, gestational age [GA] between 37 þ0 and 38 þ6 weeks) are still significant risk factors for increased morbidity and mortality after single-ventricle palliation (SVP). [1][2][3][4][5][6][7][8] Deleterious effect of younger GA may be alleviated by delaying the initial palliation, but the benefits from deferral of initial surgical palliation in terms of higher survival and lower attrition from the Fontan track are still controversial. 3,9 In this study we sought to determine the impact of GA and postmenstrual age (PMA; GA plus postnatal age) at initial palliation on surgical outcomes of SVP, focusing on the risk of interstage mortality (ISM) from each stage of the Fontan track.…”
mentioning
confidence: 99%
“…Nevertheless, considerable mortality rate in neonates rather than older children in association with corrective cardiac surgery are still challenging. Neonates needing surgical intervention early in life still have significantly higher mortality rates than infants and older children beyond the neonatal period [ 9 , 10 ]. Corrective cardiac surgery is the most responsible cause for mortality in neonates and infants [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, considerable mortality rates in neonates rather than older children in association with corrective cardiac surgery remain challenging [15]. Neonates needing surgical intervention in early life still have significantly higher mortality than infants and older children [6, 7]. Corrective cardiac surgery is one of the most major cause of mortality in neonates and infants [8].…”
Section: Introductionmentioning
confidence: 99%